Antiretroviral therapy-induced Leber's hereditary optic neuropathy - Anand Moodley; Sudika Bhola; Fierdoz Omar; Jade Mogambery (AOSIS, 2014)
Optic neuropathy in HIV-infected patients results from the HIV infection itself, post-infectious auto-immune disease, opportunistic infections and drugs. Nucleoside reverse transcriptase inhibitors (NRTIs) such as zidovudine and stavudine have known mitochondrial toxicity and can cause mitochondrial myopathies, neuropathies, hyperlactataemia, and can induce mitochondrial genetic disorders. Individuals with the mutation for Leber's hereditary optic neuropathy (LHON), a mitochondrial disorder, are usually asymptomatic but develop visual loss when exposed to external triggers such as smoking. We report on two HIV-infected patients with LHON mutations (m.14484T>C and m.11778G>A) who developed profound visual loss with antiretroviral therapy. We postulate that the phenotypic expression of LHON in these genetically predisposed individuals was triggered by NRTI drugs lamivudine and tenofovir when used in combination, despite their relatively weak mitochondrial toxic effects.